Frequency of Rare Bleeding Disorders - Naveed Khan, Nadia Kashif, Hamidullah Shah, Sabah Kaleem Baloch, Munawar Ali Shah, Fareeha Naseer Syed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The incidence and range of rare hereditary bleeding diseases, as well as the severity of the deficiency and its many clinical presentations, were the subjects of our study. Study Design: Cross-sectional study Place and Duration: Department of Pathology, Northwest School of Medicine Peshawar in the duration from July, 2022 to December, 2022. Methods: Total 850 cases of coagulation disorders were presented in this study. A thorough demographic analysis of the recruited cases was done after receiving informed written consent. After taking note of the symptoms and indicators, a coagulation profile was used to diagnose the patients. With the use of factor tests, the illness severity was evaluated. All of the data was examined using SPSS 23.0. Results: Among 850 cases, 113 (13.3%) patients were had rare bleeding disorders. In 113 cases of rare bleeding disorders, there were majority 70 (61.9%) males and 43 (38.1%) patients were females. Mean age of the cases was 10.5±13.69 years. 47 (41.6%) cases were from urban areas and 66 (58.4%) cases had rural residency. Most common deficiency was factor VII found in 33 (29.2%) cases followed by fibrinogen in 22 (19.5%) cases. 17 (15.04%) cases had family history of rare bleeding. Frequency of consanguinity was found in 88 (77.9%) cases. Most common clinical symptom was bruising, gum bleeding, epistaxis and menorrhagia. Conclusion: We concluded higher frequency of rare bleeding disorders in 13.3% cases. Factor VII deficiency is the most typical uncommon bleeding condition in our community. Due to the high rate of consanguineous marriages in our society, these bleeding diseases are very common. Keywords: Factor deficiency, Rare bleeding disorders, Factor assay, Consanguinity